Propulsive forces in human competitive swimming: a systematic review on direct assessment methods - Santos, C. C.; Marinho, D. A.; Neiva, H. P.; Costa, M. J. (Sports Biomechanics, 2021)
Human propulsive forces are a key-factor to enhance swimming performance, but there is scarce knowledge when using direct assessments. The aim of this review was to analyse the evidence about human propulsive forces in competitive swimming measured by direct assessment methods. A search up to 30 June 2020 was performed in Web of Science, PubMed, and Scopus databases. The Downs and Black Quality Assessment Checklist was used to assess the quality index (QI) of the included studies. Out of 2530 screened records, 35 articles met the inclusion criteria. Tethered-swimming and differential pressure sensors allow directly measure propulsive forces. Cross-sectional designs measured peak and mean propulsive force during the front crawl stroke and including men/boys (=15years-old) at different competitive levels were mostly reported. Men are more able to show higher propulsive forces than women counterparts. Short- and long-term effects were observed while using dry-land and in-water training programmes. The magnitude of propulsive force is dependent on the type of assessment method, swimming stroke, number of body limbs and gender. While the short-term effects supporting the different training programmes lead to an increase in propulsive force, there is a lack of long-term evidence.